2017
DOI: 10.1590/s1984-29612017063
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of coccidia of wild birds in an Atlantic forest fragment area in southeastern Brazil

Abstract: Coccidia are protozoan parasites that are frequently observed in fecal samples from wild birds, and they are extremely important for biodiversity, host specificity and conservation. The aim of the present study was to identify and quantify the coccidian species from wild birds caught in a fragmented area of Atlantic Forest in the municipality of Guapimirim in the state of Rio de Janeiro, which is located around the Serra dos Órgãos National Park. A total of 101 birds were caught and identified. The highest pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
1
Order By: Relevance
“…The birds of the two first breedings didn't show clinical signs of any type of parasite disease. In one similar study, Oliveira et al, (2017) observed that the assessed birds seem to be healthy and didn't show clinical signs usually regarded with coccidiosis, like cachexy, diarrhea and malnutrition, even those which were parasitized. In the current study, it was observed that the birds of the third breeding had feces with altered consistency, waterier than the normal, and this signal can be related with the presence of coccidia found in the exams, this relation was also verified by Penha et al (2008).…”
Section: Resultsmentioning
confidence: 92%
“…The birds of the two first breedings didn't show clinical signs of any type of parasite disease. In one similar study, Oliveira et al, (2017) observed that the assessed birds seem to be healthy and didn't show clinical signs usually regarded with coccidiosis, like cachexy, diarrhea and malnutrition, even those which were parasitized. In the current study, it was observed that the birds of the third breeding had feces with altered consistency, waterier than the normal, and this signal can be related with the presence of coccidia found in the exams, this relation was also verified by Penha et al (2008).…”
Section: Resultsmentioning
confidence: 92%
“…The largest number of coccidium was detected through fecal examination in domestic pigeons (13/22, 59.1%) in this study. Research studies conducted in other countries such as China, India and United States of America have shown that the prevalence rate of coccidium in domestic pigeons varies from at least 10% up to 90% (4,9,10,11). Such a high prevalence rate of coccidium in domestic pigeons might be due to the low pathogenicity of coccidium and life styles of pigeons living in groups (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…In the Alps, the construction of ski-pistes has widely impacted the ecosystem, with a negative ‘edge effect’ on wild bird populations (Caprio et al ., 2014 ). In addition to the direct impacts on fauna, flora and microbiota, the edge effect favours transmission of parasites to wild birds and susceptibility to parasites among wild birds (Oliveira et al ., 2017 ). The negative effect of the presence of ski areas have been also demonstrated by Belleau ( 2013 ), in another study reporting a higher prevalence of C. caudinflata in Galliformes coming from human disturbed habitats.…”
Section: Discussionmentioning
confidence: 99%